Transanastomotic Feeding Tube in Surgical Management of Congenital Duodenal Obstruction: Case Series - Gunardi, Hardian; Rachmawati, Asri D; Susilo, Nanok E; Tamba, Riana P (The New Ropanasuri Journal of Surgery, 2020)
Introduction. Prolonged fasting is a major concern in the postoperative management of congenital duodenal obstruction. Massive dilatation of the proximal segment would lead to diameter discrepancy and lack of propulsion, thus delaying enteral feeding. A transanastomotic feeding tube is an option to deliver early enteral feeding after surgical correction. The study evaluates the effectiveness and safety of a transanastomotic feeding tubes in the surgical management of congenital duodenal obstruction. Method. The transanastomotic feeding tube's effectiveness in cases of congenital duodenal obstruction of the newborn underwent surgical correction was evaluated. Those managed from January 2016 to December 2018 at dr. Cipto Mangunkusumo and Fatmawati General Hospital were subjected to the evaluation. Results. Ten cases were recorded, with the mean gestational age of 30.4 weeks (SD ± 2.12), with a mean bodyweight of 2.571 g (SD ± 392). Seventy percent of the cases accompanied by other anomalies. Enteral nutrition was introduced immediately after surgery. The median time of oral nutrition initiation was 13 days (3-21), and the patients were fully fed in 19.5 days (13-37). The average length of stay was 24.5 days (16-40 days). One case had a complication requiring surgery, and mortality in two cases complicated with sepsis. Conclusion: Transanastomotic feeding tube is an option to deliver early enteral feeding after surgical correction of congenital duodenal obstruction.